Meeting Belongingness Needs: An Inclusive Leadership Practitioner's Approach. Issue 4 (November 2022) - Canlas, Aimee L.; Williams, Michael R.
Problem: Theoretical and practical frameworks delineating the individual and relational needs inherent to creating perceptions of belongingness in the workplace are absent in Human Resources Development (HRD) literature. For inclusive leadership practitioners, the literature itself lacks direct mentioning of belonging, causing the awareness around the concept to be problematic. Without a clear understanding of factors that influence perceptions of belonging, leaders lack direction in building inclusive workplaces and reaping the beneficial business outcomes these have the potential to bring, including increased employee engagement, performance, and innovation. Solution: The Individual and Relational Belongingness (IRB) model is introduced to explore and define the unique needs that are vital for individual to perceive a sense of belongingness in the workplace across individual, relational, personal, and organizational dimensions. Stakeholders: Organizational and Human Resources Development scholar practitioners benefit from understanding the nuanced and complex needs that drive perceptions of belongingness, since these bring additional context to the scholarship and practice of inclusive leadership.